Understanding the impact of cross-group friendship on interactions with novel outgroup members. [article]. - Page-Gould, Elizabeth
We examined the cognitve processes that might account for the impact of cross-group friendship on novel intergroup situations. Study 1 demonstrated that closeness with outgroup predicts an association of the outgroup with the self, both in terms of the group itself and the personality traits stereotypically associated with the group. In studies 2 and 3, we manipulated the accessibility of eithera same-group friendship or cross-group friendship. Participants who described a cross-group friend exhibited a greater association of the friend's ethnicity with the self, and this association mediated the effects of friendship accessibility on positive expectations for intergroup contact (Study n2) and adaptive harmonal responses during a real interaction with a novel intergroup experiences to the degree that outgroups become associated with the self.